PENGGUNAAN MEDIA KONKRET DALAM PEMBELAJARAN MATEMATIKA DI SEKOLAH DASAR - Maifit Hendriani (LP2M Universitas Adzkia, 2021)
Abstract The learning process is a process in which there are interaction activities between teachers and students as well as reciprocal communication that takes place in educational situations to achieve learning objectives. The facilities and facilities used in the learning process greatly affect learning outcomes, one of which is learning media. The use of concrete media in the teaching and learning process can clarify the presentation of messages and information so as to facilitate and improve learning processes and outcomes. The purpose of this study was to determine the use of concrete media for learning mathematics in elementary schools. This research is a qualitative descriptive study to describe the use of concrete media for learning Mathematics in Elementary Schools. Sources of data in this study are books and research journals that have been published. Data collection techniques using literature study and documentation. The results of this study indicate that the use of concrete media in learning mathematics in elementary schools can support student learning outcomes so that they get maximum results. Students in elementary school are at the stage of concrete thinking, where their mindset will tend to catch something that is concrete or real. With the concrete media students are not only able to understand the concepts in learning Mathematics, but are also able to think critically and logically in the face of learning. Keywords: Concrete Media, Mathematics.